1999
DOI: 10.1002/(sici)1097-4628(19990321)71:12<1969::aid-app6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A study of chemical structure of soft and hardwood and wood polymers by FTIR spectroscopy

Abstract: ABSTRACT:Hard and softwood and wood constituent polymers (cellulose and lignin) were studied using Fourier transform infrared (FTIR) spectroscopy. The hollocelluloseto-lignin ratio was estimated for some of the timber species. The structural difference between Klason lignin isolated from softwood (Pinus roxberghii and cupressus lusitanica) and hard wood (Acacia auriculaeformis and Eucalyptus tereticornis) species was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
490
1
20

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,024 publications
(585 citation statements)
references
References 10 publications
39
490
1
20
Order By: Relevance
“…The increase in the intensity of the 1600 cm -1 band may indicate quinine formation by irradiation during accelerated ageing which was found at around 1650 cm -1 region by other researchers [30]. The bands at 1734 and 1600 cm -1 are characteristic absorptions of carbonyl stretching vibrations of non-conjugated (in xylan) and conjugated (in lignin) esters and carboxylic acids, and their concentration increases as carbonyl groups are liberated from lignin and/or carbohydrates due to chemical degradation [30][31][32]. Pure PLA has a C-H deformation band at 1350 to 1460 cm -1 , which was found to be at 1400 cm -1 for both control and accelerated aged samples [17].…”
Section: Fourier Transform Infrared (Ftir) Spectra Analysismentioning
confidence: 96%
“…The increase in the intensity of the 1600 cm -1 band may indicate quinine formation by irradiation during accelerated ageing which was found at around 1650 cm -1 region by other researchers [30]. The bands at 1734 and 1600 cm -1 are characteristic absorptions of carbonyl stretching vibrations of non-conjugated (in xylan) and conjugated (in lignin) esters and carboxylic acids, and their concentration increases as carbonyl groups are liberated from lignin and/or carbohydrates due to chemical degradation [30][31][32]. Pure PLA has a C-H deformation band at 1350 to 1460 cm -1 , which was found to be at 1400 cm -1 for both control and accelerated aged samples [17].…”
Section: Fourier Transform Infrared (Ftir) Spectra Analysismentioning
confidence: 96%
“…The development of fourier transform infrared (FTIR) microscopy, with its non-destructive and rapid technique that surpasses conventional techniques, enabled studies on wood and other lignocellulosics' surface characterisation, as well as lignin and carbohydrate content evaluation. The conventional method is laborious and destructive to natural polymer (Pandey 1999).…”
Section: Neighbourhood Of Vessels: Chemical Composition and Microfibrmentioning
confidence: 99%
“…19 -24 In addition, FTIR was employed to study functional groups in wood. [25][26][27] The results of the study reported here will aid in the development of an understanding of how processing methods affect color fade and mechanical properties of wood-flour/HDPE composites after weathering.…”
Section: Introductionmentioning
confidence: 99%